Che cosa significa orientarsi agli oggetti? - Pisano, Francesco (Mechane, 2020)
The paper discusses some aspects of Object-Oriented Ontology (OOO) as a philosophical research program. The discussion stems from a reading of Decentrare l’umano. Perché la Object-Oriented Ontology (Kaiak 2021), a collection of essays that aims at introducing the Italian reader to the debate surrounding OOO. Working both as an introduction and as a critical discussion, Decentrare l’umano highlights the main tenets of OOO and some of their problematic implications. It does so through both theoretical arguments and imaginative literary performances played out by some of the collected essays. Adopting a Kantian point of view, I argue that such a pluralistic approach to OOO rightly shows the need for an “Object-Oriented critique” that should put OOO in question as a theory, i. e. as a discursive product, without losing sight of OOO’s appeal to realism, concreteness, and directedness.